Pergeseran Pola Belajar Santri Dayah di Aceh - Firdaus M. Yunus (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2021)
In the past decade, at least there are five types of dayah have developed in Aceh. These five types of dayah apply different teaching patterns to their students. The first type is the traditional one, which maintains the old pattern in educating the students. The second type is modern dayah; in this dayah, the learning pattern is planned and refers to the specified curriculum. The third type is a kind of dayah, which combines traditional and modern learning systems. In this dayah, students are not required to stay overnight. They are allowed to go home. The fourth style is the dayah of tahfizul Quran; in this dayah, the students only focus on studying and memorizing the Quran. Furthermore, the fifth style of dayah is the dayah of tahfizul Quran and hadith, where the students at this dayah focused on memorizing the Qur'an and the hadith. The last two features of the dayah are developing rapidly in Aceh. This study employs a qualitative approach. For data needs, the researcher conducted the interview, observation, and documentation. This study found that Acehnese people in several regions showed that they were still very interested in traditional dayahs, even though the current modern dayah increasingly grows in Aceh. Secondly, modern dayahs that apply different learning patterns cause many parents to be more interested in modern dayahs. Thirdly, the emergence of the dayah Tahfizul Quran and Tahfizul Hadith become a new choice for parents to encourage their children to become memorizers of the Quran and hadith.